Naming the land : San identity and community conservation in Namibia's West Caprivi - Taylor, Julie J. (Julie Jennifer), 1980- (Basel Namibia studies series ;, 2012)
This book encompasses a history of identity-building amongst Khwe San people, and of contestations for authority over land and natural resources in Namibia's West Caprivi. The politics of authority in this contested borderland area were significantly shaped by state and NGO interventions into local institutions and land use between the late 1930s and 2006. Julie J. Taylor pays close attention to the role of NGOs in these processes. She shows that, in their relationship with West Caprivi's residents, NGOs unintentionally contributed towards the hardening and politicising of ethnic difference, including through the implementation of land mapping projects. At the same time, in their relationship with the state, NGOs often worked to 'depoliticise' struggles over authority, thus inadvertently reinforcing the state's authority in the area.